The use of meeting tools to make an online event: The CTRL+E experience - Medeiros, Elizabet M. Spohr de; Villacorta, Kely D. V.; Moreno, Felipe A. G.; Salviano, Artur I. A.; Silva, Matheus Gomes; Pedrosa, João Victor; Cavalcanti, Daniel de Queiroz; Nascimento, Matheus W. T. (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2021)
This article describes the experience acquired in the use of tools for recording remote meetings, video editing and transmissions used in the execution of CTRL+E 2020, transforming it into a 100% online event.